Gem‐Difluorination of Alkenyl N‐methyliminodiacetyl Boronates: Synthesis of α‐ and β‐Difluorinated Alkylborons. Issue 50 (12th November 2018) - Lv, Wen‐Xin; Li, Qingjiang; Li, Ji‐Lin; Li, Zhan; Lin, E; Tan, Dong‐Hang; Cai, Yuan‐Hong; Fan, Wen‐Xin; Wang, Honggen
Abstract: Organofluorine compounds are widely used in pharmaceutical, agrochemical, and materials sciences. The syntheses and applications of fluorinated organoborons facilitate the rapid and modular assemblies of fluorine‐containing molecules because of the versatility of C−B bonds in diverse chemical transformations. Reported herein is a migratory geminal difluorination of aryl‐substituted alkenyl N ‐methyliminodiacetyl (MIDA) boronates using commercially available Py⋅HF as the fluorine source and hyperiodine as the oxidant. The protocol offers facile access to α‐ and β‐difluorinated alkylboron compounds, both of which have previously been challenging to prepare. Mild reaction conditions, broad substrate scope, good functional‐group tolerance, and moderate to good yields were observed. The utility of these products is demonstrated by further transformations of the C−B bond into other valuable functional groups. Abstract : On the move : A migratory geminal difluorination of aryl‐substituted alkenyl N ‐methyliminodiacetyl (MIDA) boronates using commercially available Py⋅HF as the fluorine source is reported. The protocol offers an unprecedented opportunity for the synthesis of α‐ and β‐difluorinated alkylboron compounds. Mild reaction conditions, broad substrate scope, good functional‐group tolerance, and moderate to good yields were observed.